2004
DOI: 10.1021/bp0342203
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic Stress in Murine Hybridoma Cells: Effects on Antibody Transcription, Translation, Posttranslational Processing, and the Cell Cycle

Abstract: Mechanisms for increased antibody production in batch cultures of murine hybridoma cells in response to hyperosmotic stress were investigated. The rates of immunoglobulin transcription and protein translation and posttranslational processing were determined in control and hyperosmotic cultures. Changes in immunoglobulin transcription played a minor role in the increase in antibody production in response to hyperosmotic stress. In contrast, protein translation increased substantially in response to osmotic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 61 publications
(80 reference statements)
4
33
1
Order By: Relevance
“…An additional optimization strategy would be prevention of the onset of apoptosis after cessation of growth, at which time cells are accumulating in the G1 cell cycle phase. Identification of regulatory mechanisms for cell cycle progression and of associated environmental manipulation are emerging areas of research (Balcarcel and Stephanopoulos 2001;Bjorklund et al 2006;Carvalhal et al 2003;deZengotita et al 2001;Ibarra et al 2003;Sun et al 2004;Sunstrom et al 2000).…”
Section: Recombinant Protein Productivity As a Function Of Cell Cyclementioning
confidence: 99%
“…An additional optimization strategy would be prevention of the onset of apoptosis after cessation of growth, at which time cells are accumulating in the G1 cell cycle phase. Identification of regulatory mechanisms for cell cycle progression and of associated environmental manipulation are emerging areas of research (Balcarcel and Stephanopoulos 2001;Bjorklund et al 2006;Carvalhal et al 2003;deZengotita et al 2001;Ibarra et al 2003;Sun et al 2004;Sunstrom et al 2000).…”
Section: Recombinant Protein Productivity As a Function Of Cell Cyclementioning
confidence: 99%
“…The transcription levels of both heavy chain (HC) and light chain (LC) mRNAs are enhanced as well as antibody productivity [6]. The increase of the post-translational processing rate appears to be commensurate with that of antibody production in response to hyperosmotic stress [7]. Recently, a genome-wide analysis has been performed to investigate the transcriptional response of hybridoma cells towards hypertonic stress using DNA microarrays [8].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 58 reported that the enhancement of the specific thrombopoietin productivity is linearly correlated with the increase in cell size for nine CHO cell clones generated using the same transfection process. In a number of studies the relation between cell size and specific productivity was used to enhance mAb productivity, by directly or indirectly increasing the cell size, for example, through cell cycle arrest 53,91 , hyperosmotic pressure 92,93 , and mild hypothermia 57,94 . Acetic acid and formic acid accumulation were observed during the cultures (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…The result agrees with the fact that after day 5 cell proliferation has stopped in the ActiCHO process (Figure 1). In several CHO cell culture processes, hypothermia 19,127,128 , hyperosmotic stress 92,129 , and cell cycle inhibitors 53,91,130 were applied that mediated a G0/G1 arrest without influencing G2/M phase. This was, however, not the case in the present study where cell cycle arrest occurred in both G0/G1 and the G2/M phase.…”
Section: Cell Growth Cell Size and Cell Cycle Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation